Choroidal expansion as a mechanism for acute primary angle closure: an investigation into the change of biometric parameters in the first 2 weeks. Issue 3 (17th February 2005) - Yang, M; Aung, T; Husain, R; Chan, Y-H; Lim, L S; Seah, S K L; Gazzard, G
Abstract : Background/aim: Choroidal expansion with anterior movement of the lens was recently proposed as a mechanism for acute primary angle closure (APAC). The aim of this study was to compare the biometric parameters, central anterior chamber depth, limbal chamber depth, lens thickness, and lens position, within 24 hours of presentation and 2 weeks later in eyes with APAC. Methods: This was a prospective observational case series of 41 subjects with APAC. Subjects who presented with APAC were treated with medical therapy followed by laser iridotomy (LI) in both eyes once the acute attack was broken. Ocular biometry was performed in affected and fellow eyes before LI (baseline) and then 2 weeks later. Optical pachymetry was used to measure central anterior chamber depth (ACD) and the limbal chamber depth (LCD) was graded at the slit lamp. A-scan ultrasound was used to measure lens thickness (LT) and axial length (AL). Lens position (LP) was defined as ACD +½LT. Results: The majority of subjects were Chinese (83%) and female (61%), and the mean age was 60.4 (SD 10.3) years. In affected eyes, the ACD was 1.81 (0.29) mm before and 1.80 (0.28) mm 2 weeks after LI (p = 0.63), while in fellow eyes, the ACD was 1.83 (0.29) mm and 1.81 (0.38) mm, respectively (p = 0.21). There was no significant change in lens position, relative lens position, or axial length in both affected and fellow eyes over the 2 weeks. Conclusions: There was no change observed in central anterior chamber depth, lens thickness, or lens position at the time of the acute attack compared to 2 weeks later in both APAC affected and fellow eyes. The findings do not support the hypothesis of lens movement due to choroidal expansion in APAC.